"Transition-metal-free" synthesis of carbazoles by photostimulated reactions of 2′-halo[1,1′-biphenyl]-2-amines - Guerra, Walter Damián (2014)
An efficient and simple protocol for the preparation of a series of 9H-carbazoles by photostimulated SRN1 substitution reactions is presented. Substituted 9H-carbazoles were synthesized in low to excellent yields (up to 96%) through an intramolecular C-N bond formation of 2′-halo[1,1′-biphenyl]-2-amines by the photoinitiated SRN1 mechanism under mild and "transition-metal-free" conditions. The biphenylamines used as substrates were obtained with isolated yields ranging from 21% to 84% by two approaches: (A) the cross-coupling Suzuki-Miyaura reaction and (B) the radical arylation of anilines. Some key aspects of the proposed mechanism were evaluated at the B3LYP/6-311+G∗ level.